Exercise reduces circulating biomarkers of cellular senescence in humans. Issue 7 (8th June 2021) - Englund, Davis A.; Sakamoto, Ayumi E.; Fritsche, Chad M.; Heeren, Amanda A.; Zhang, Xu; Kotajarvi, Brian R.; Lecy, Denise R.; Yousefzadeh, Matthew J.; Schafer, Marissa J.; White, Thomas A.; Atkinson, Elizabeth J.; LeBrasseur, Nathan K.
Abstract: Cellular senescence has emerged as a significant and potentially tractable mechanism of aging and multiple aging‐related conditions. Biomarkers of senescent cell burden, including molecular signals in circulating immune cells and the abundance of circulating senescence‐related proteins, have been associated with chronological age and clinical parameters of biological age in humans. The extent to which senescence biomarkers are affected by interventions that enhance health and function has not yet been examined. Here, we report that a 12‐week structured exercise program drives significant improvements in several performance‐based and self‐reported measures of physical function in older adults. Impressively, the expression of key markers of the senescence program, including p16, p21, cGAS, and TNFα, were significantly lowered in CD3 + T cells in response to the intervention, as were the circulating concentrations of multiple senescence‐related proteins. Moreover, partial least squares discriminant analysis showed levels of senescence‐related proteins at baseline were predictive of changes in physical function in response to the exercise intervention. Our study provides first‐in‐human evidence that biomarkers of senescent cell burden are significantly lowered by a structured exercise program and predictive of the adaptive response to exercise. Abstract : Our study provides first‐in‐human evidence that biomarkers of senescent cell burden are significantly lowered by a structured exercise program and predictive of the adaptive response to exercise.